2013 Seventh International Conference on Next Generation Mobile Apps, Services and Technologies 2013
DOI: 10.1109/ngmast.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Throughput Optimization for Cooperative Spectrum Sensing in Cognitive Radio Networks

Abstract: In this paper, the channel utilization (throughput vs sensing time relationship) is analyzed for cooperative spectrum sensing under different combining rules and scenarios. The combining rules considered in this study are the OR hard combining rule, AND the hard combining rule, the Equal Gain Soft combining rule and the two-bit quantized (softened hard) combining rule. For all combining rules, the detection performance, with a Gaussian distribution assumption, is expressed in two different scenarios, CPUP (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…It is also important to note that most of the research efforts on different fusion rules for cooperative sensing are analytical and/or Matlab simulations based [3]- [5]. Recently a few measurement-based studies on cooperative sensing can be found in [6]- [8].…”
Section: This Paper Is a Revised And Expanded Version Of The Paper Prmentioning
confidence: 99%
“…It is also important to note that most of the research efforts on different fusion rules for cooperative sensing are analytical and/or Matlab simulations based [3]- [5]. Recently a few measurement-based studies on cooperative sensing can be found in [6]- [8].…”
Section: This Paper Is a Revised And Expanded Version Of The Paper Prmentioning
confidence: 99%
“…In the propose model we have used OR rule because it has better detection performance when the number of cooperating CR users is large. [12], and provides slightly better performance at low Pf [13].…”
Section: Introductionmentioning
confidence: 97%
“…DFC combines those decisions and makes a final decision [18]. Different conventional diversity techniques are used to combine the independent decision which are discussed in [19] and [20]. In this paper, we have considered Maximal Ratio Combining (MRC) scheme with Energy and Bayesian detection.…”
Section: Introductionmentioning
confidence: 99%